(untitled) (Nigerian Journal of Cooperative Economics and Management, 2026)
Cooperative societies are widely recognised as key institutions for rural development; however, cocoa farmers in Idanre, Ondo State continue to experience low income levels, weak asset ownership, and persistent food insecurity despite their participation in cooperative systems. This study therefore examines the effect of cooperative societies on poverty alleviation among cocoa farmers in Idanre, Ondo State. The specific objectives are to: (i) determine the effect of agricultural marketing cooperatives on income level; (ii) assess the impact of credit and thrift cooperatives on asset ownership; and (iii) examine the influence of multipurpose cooperative societies on food security among cocoa farmers. A survey research design was adopted, and data were collected from a sample of 250 registered cocoa farmers selected through stratified and simple random sampling techniques. Structured questionnaires were used for data collection. Descriptive and inferential statistics were employed, while multiple regression analysis was used to test the hypotheses with the aid of SPSS version 25. The findings revealed that agricultural marketing cooperatives significantly enhance income levels, agricultural credit and thrift cooperatives improve asset ownership and economic stability, while multipurpose cooperative societies significantly enhance food security among rural households. The study concludes that cooperative societies contribute to poverty alleviation among cocoa farmers and recommends strengthened cooperative structures, improved credit access, capacity building, and supportive government policies for sustainable rural development.